Leptomeningeal Contrast Enhancement Is Associated with Disability Progression and Grey Matter Atrophy in Multiple Sclerosis - Gleb Makshakov; Evgeniy Magonov; Natalia Totolyan; Vladimir Nazarov; Sergey Lapin; Alexandra Mazing; Elena Verbitskaya; Tatiana Trofimova; Vladimir Krasnov; Maria Shumilina; Alexander Skoromets; Evgeniy Evdoshenko (Neurology Research International)
Leptomeningeal contrast enhancement (LMCE) on magnetic resonance imaging (MRI) is a newly recognized possible biomarker in multiple sclerosis (MS), associated with MS progression and cortical atrophy. In this study, we aimed to assess the prevalence of LMCE foci and their impact on neurodegeneration and disability. Materials. 54 patients with MS were included in the study. LMCE were detected with a 3 Tesla scanner on postcontrast fluid-attenuated inversion-recovery (FLAIR) sequence. Expanded Disability Status Scale (EDSS) score, number of relapses during 5 years from MS onset, and number of contrast-enhancing lesions on T1 weighted MRI were counted. Results. LMCE was detected in 41% (22/54) of patients. LMCE-positive patients had longer disease duration (p=0,0098) and higher EDSS score (p=0,039), but not a higher relapse rate (p=0,091). No association of LMCE with higher frequency of contrast-enhancing lesions on T1-weighted images was detected (p=0,3842). Analysis of covariates, adjusted for age, sex, and disease duration, revealed a significant effect of LMCE on the cortex volume (p=0.043, F=2.529), the total grey matter volume (p=0.043, F=2.54), and total ventricular volume (p=0.039, F=2.605). Conclusions. LMCE was shown to be an independent and significant biomarker of grey matter atrophy and disability in MS.